Functionality Study of an Optical Measurement Concept for Local Force Signal Determination in High Strain Rate Tensile Tests - Böhnke, Max; Unruh, Eduard; Sell, Stanislaw; Bobbert, Mathias; Hein, David; Meschut, Gerson (Key Engineering Materials)
Many mechanical material properties show a dependence on the strain rate, e.g. yield stress or elongation at fracture. The quantitative description of the material behavior under dynamic loading is of major importance for the evaluation of crash safety. This is carried out using numerical methods and requires characteristic values for the materials used. For the standardized determination of dynamic characteristic values in sheet metal materials, tensile tests performed according to the guideline from [1]. A particular challenge in dynamic tensile tests is the force measurement during the test. For this purpose, strain gauges are attached on each specimen, wired to the measuring equipment and calibrated. This is a common way to determine a force signal that is as low in vibration and as free of bending moments as possible. The preparation effort for the used strain gauges are enormous. For these reasons, an optical method to determine the force by strain measurement using DIC is presented. The experiments are carried out on a high speed tensile testing system. In combioantion with a 3D DIC high speed system for optical strain measurement. The elastic deformation of the specimen in the dynamometric section is measured using strain gauges and the optical method. The measured signals are then compared to validate the presented method. The investigations are conducted using the dual phase steel material HCT590X and the aluminum material EN AW-6014 T4. Strain rates of up to 240 s-1 are investigated.
Keywords: Mechanical Engineering; Mechanics of Materials; General Materials Science

Analytische Auslegung der Schwingfestigkeit geclinchter Verbindungen - Unruh, Eduard; Hein, David; Meschut, Gerson (10. Fügetechnisches Gemeinschaftskolloquium)

Charakterisierung und Modellierung von Kerbeffekten durch Mischverbindungen in Karosseriebauteilen aus höchstfesten Stählen - Bähr, Philipp; Sommer, Silke; Unruh, Eduard; Hein, David; Meschut, Gerson

Charakterisierung und Modellierung von Kerbeffekten durch Mischverbindungen in Karosseriebauteilen aus höchstfesten Stählen - Unruh, Eduard; Hein, David; Meschut, Gerson; Bähr, Philipp; Sommer, Silke (9. Fügetechnisches Gemeinschaftskolloquium)

Analytische Auslegung der Schwingfestigkeit geclinchter Verbindungen - Unruh, Eduard; Hein, David; Meschut, Gerson (9. Fügetechnisches Gemeinschaftskolloquium)